Design and Build Applications in Total Forecasting New Students in School by Applying Non Linear Trend Method - Lola Eris Monika; Yupianti Yupianti; Rizka Tri Alinse (Jurnal Komputer, Informasi dan Teknologi, 2021)
SMA Muhammadiyah 1 Bengkulu City is one of the schools located in Bengkulu City, where several data processing systems still use manual systems, one of which is new student registration. Every new school year, the officer fills out the sheet of students enrolled in the school one by one in the registration book. This takes a long time when the officer wants to make a report of students registered, because they have to retype the data in the registration book into the computer. In addition, after conducting interviews, it was found that the students at SMA Muhammadiyah 1 Bengkulu City experienced a decline every academic year. The application of forecasting the number of new students at SMA Muhammadiyah 1 Bengkulu City can be used to predict the number of new students in the next academic year based on the results of the analysis on old historical data. This forecasting process is carried out through the Non-Linear Trend Method approach, so that the final forecasting result is obtained from the stages of the process that occur. It was made using the VB.Net programming language and SQL Server database which can assist the school in managing school quality assurance, in order to attract interest from prospective students to enroll in SMA Muhammadiyah 1 Bengkulu City, and can arrange school promotion strategies for prospective students. Based on the tests that have been carried out, it can be concluded that the functional application of forecasting the number of new students at SMA Muhammadiyah 1 Bengkulu City has been running properly and the application for forecasting the number of new students at the school which is able to display forecasting results in the next academic year.